2016
DOI: 10.5014/ajot.2016.018291
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Electrodermal Activity: Quantifying Sensory Processing in Children With Autism

Abstract: EDA measures are reliable physiological markers that can quantify response to sensation in children with and without ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…The overlapping confidence intervals of ICC indicate that the reliability of both measures does not differ between the two groups. These findings are comparable to test–retest reliability of HR/HRV in preschoolers [Doussard‐Roosevelt, Montgomery, & Porges, ], brain measures in children [Somandepalli et al, ], and electrodermal activity in ASD [Schupak, Parasher, & Zipp, ]. The reliability of HR/HRV suggests that there are trait‐like individual differences in regulation of arousal state in children with ASD and maybe promising for the use of cardiac activity as a biomarker for individual difference in preschoolers.…”
Section: Discussionsupporting
confidence: 57%
“…The overlapping confidence intervals of ICC indicate that the reliability of both measures does not differ between the two groups. These findings are comparable to test–retest reliability of HR/HRV in preschoolers [Doussard‐Roosevelt, Montgomery, & Porges, ], brain measures in children [Somandepalli et al, ], and electrodermal activity in ASD [Schupak, Parasher, & Zipp, ]. The reliability of HR/HRV suggests that there are trait‐like individual differences in regulation of arousal state in children with ASD and maybe promising for the use of cardiac activity as a biomarker for individual difference in preschoolers.…”
Section: Discussionsupporting
confidence: 57%
“…As previously reported in older children with ASD [Fenning et al, 2017;Fenning et al, 2019;Goodwin, 2016;Schupak, Parasher, & Zipp, 2016], the current results demonstrate that changes in ambulatory EDA response is a feasible and valid measure of peripheral physiological arousal during more naturalistic situations in very young ASD and TD children. Capitalizing on the accessibility and usability of newer mobile sensors (able to measure multiple physiological markers simultaneously) to concurrently examine larger groups of children would provide this more complete picture and help replicate, support, and extend our study with its relatively large but population-modest sample size.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, since EDA solely reflects activity of the sympathetic nervous system, it would be beneficial to simultaneously assess the parasympathetic branch given its role in emotion regulation and assistance in recovering from stressful events [Langley, 1921]. This could be achieved by combining more than a few physiological indicators such as heart rate variability or blood pressure [Kushki et al, 2013;Levine et al, 2012;Schupak et al, 2016] to get a more complete picture of the full autonomic response profiles present in toddlers with ASD. Given the association between physiological and behavioral response observed during the Joy condition in toddlers with ASD in the current study, future investigations of physiological reactivity to joyful situations in ASD would benefit from utilization of toys or specific interests thought to trigger positive emotions.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, of the three studies that used EDA as the physiological autonomic measure, only one component was found to be similar across (i.e., EDA magnitude) and other EDA components differed. While autonomic measures may be a good index of physiological responses, each would have a function specific to a related behavioural response that needs to be considered in future research designs [ 28 , 39 , 54 ]. The choice of experimental laboratory paradigm to elicit physiological responses poses a great influence on the methodological robustness and eventual uniformity and generalizability of findings across the studies [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…While autonomic measures may be a good index of physiological responses, each would have a function specific to a related behavioural response that needs to be considered in future research designs [ 28 , 39 , 54 ]. The choice of experimental laboratory paradigm to elicit physiological responses poses a great influence on the methodological robustness and eventual uniformity and generalizability of findings across the studies [ 54 ]. Two of the reviewed studies [ 5 , 31 ] used the Sensory Challenge Protocol, while the rest used their own novel sensory paradigm.…”
Section: Discussionmentioning
confidence: 99%